2019
DOI: 10.1007/s11195-019-09597-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Health Communication Between Healthcare Professionals and Adolescents with Chronic Conditions in Western Countries: An Integrative Review

Abstract: Adolescent patients and healthcare professionals find it difficult to initiate the discussion on sexual health in consultations. The aim of this integrative review is to give an overview of determinants in the communication about sexual health between adolescents with chronic conditions, their parents, and their healthcare professionals. A systematic literature search for the period of January 2000 to October 2018 was conducted in four databases (Cinahl, Cochrane, PsycINFO, and Pubmed) and resulted in fifteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…A substantial number of women (30.1%) had complaints of dyspareunia, more than expected from the background rate of 21% 20 . Although illness can have a large impact on sexuality, the topic is often overlooked by healthcare professionals – initiating discussion of the subject could help to normalise the subject and to provide patient education and treatment options 21 . The most frequently mentioned physical complaint in the qualitative analysis is long‐term fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of women (30.1%) had complaints of dyspareunia, more than expected from the background rate of 21% 20 . Although illness can have a large impact on sexuality, the topic is often overlooked by healthcare professionals – initiating discussion of the subject could help to normalise the subject and to provide patient education and treatment options 21 . The most frequently mentioned physical complaint in the qualitative analysis is long‐term fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, men's desires, demands and expectations are often beyond the expected competences of HPs, since previous studies showed that HPs lack education and competences in the field of sexuality. [15][16][17][18] To meet the needs of men in cardiovascular secondary prevention and rehabilitation, HPs should be professional, educated, and competent in this field. Another ethical aspect was the men's concerns about their own and other men's integrity and boundaries regarding HPs' address of sexuality, ED and i-PAVED.…”
Section: Discussionmentioning
confidence: 99%
“…13 Common barriers for HPs' address of sexuality and sexual issues such as ED are due to lack of HP education, competences and professionalism in the field of sexuality, or HPs' perception that addressing sexuality is embarrassing for patients, being too intimate, private and potentially offensive to discuss. [14][15][16][17][18] Furthermore, HPs' reason for not inquiring about sexual function and ED can be attributed to their impression of cardiac patients' lack of readiness and reluctance to bring up the subject. 14,18,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erectile dysfunction (ED) often remains overlooked, underdiagnosed and under-treated by health professionals (HPs) [1][2][3][4] who rarely discuss ED with men [5,6]. However, there is increasing recognition of the role of low-risk, lowcost, non-pharmacological and safe lifestyle interventions to lessen the burden of vascular ED [7][8][9].…”
Section: Introductionmentioning
confidence: 99%